Crystal structure, electrical and electrochemical properties of Cu co-doped Pr1.3Sr0.7NiO4+δ mixed ionic-electronic conductors (MIECs). (4th January 2018) - Bansod, M.B.; Khandale, A.P.; Kumar, R.V.; Bhoga, S.S.
Abstract: Room temperature crystal structure, electrical properties and electrochemical properties in the temperature range 25–700 °C of Cu co-doped Pr1.3 Sr0.7 NiO4+ δ prepared by acetate combustion is investigated from intermediate temperature solid oxide fuel cell cathode viewpoint. The Pr1.3 Sr0.7 Ni1−x Cux O4+ δ (PSNCO) solid solutions have a tetragonal I 4 /mmm K2 NiF4 -type structure which consists of a (Pr1.3 Sr0.7 ) (Ni1.x Cux )O3 perovskite unit and a (Pr1.3 Sr0.7 )O rock salt unit in the whole compositional range 0 ≤  x  ≤ 0.4. A reduction in bond-length of Ni/Cu-O resulting from PSNCO lattice contraction eases hop of small polaron from Ni 3+ to Ni 2+ /Cu 2+ in (Ni1−x Cux )-O layer with low activation energy, which increases electron conductivity. The maximum electronic conductivity ( σ  = Ω cm −1 ) with minimum activation energy ( E a  = eV) is observed at x  = 0.3. Lattice expansion along c -direction owing to Cu 2+ doping facilitates hop of O 2− from its occupied interstitial site (O3 ) to nearby equivalent site assisted by anisotropic thermal motion of apical oxygen O2 resulting in increase in ionic conductivity. The minimum polarization resistance value ( R p  = 0.13 (2) Ω cm 2 ) and activation energy ( E a  = 1.321 (5) eV) at x  = 0.3 is attributed to high electronic and ionic conductivities compared to other compositions. Complex impedance spectroscopy studies suggest that the ORR is co-limited by O 2− diffusion and O2 surface exchange. Graphical abstract: Highlights: Cu co-doped Pr1.3 Sr0.7 NiO4+ δ synthesized by combustion yield super fine crystallites. Lattice contraction along a - b directions by co-doping facilitates small polaron hopping. Surface oxygen exchange reaction increases with Cu doping. CIS study suggests ORR is co-limited by O 2− diffusion and O2 surface exchange.